Transmission mechanisms in Japan’s quantitative easing policy (2001–2006) - Ijiri, Hiroyuki (Economics and Business Letters, 2017)
This study investigates exchange rates and bank lending as the transmission channels for Japan’s Quantitative Easing Policy (QEP) during 2001–2006. Using a Time Varying Parameter-VAR model and monthly data to analyze the dynamism of the QEP, this study is the first to show that the exchange rate channel was the eﬀective QEP transmission channel after around 2005, while the bank lending channel was inactive.